2019
DOI: 10.2139/ssrn.3489371
|View full text |Cite
|
Sign up to set email alerts
|

Latent Work Capacity and Retirement Expectations

Abstract: Understanding how health decline influences retirement decisions is fundamental for the design of targeted policies that encourage working longer. While there is wide agreement on the relevance of age-related health decline for determining labor supply and retirement decisions, the process of how health deterioration affects labor supply remains a black box. This paper explores the match between individuals' functional abilities and job demands in the national economy using a new methodology to measure work ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In this paper, we use RML adoption as a large shock to the availability of an alternative form of chronic pain management, in particular one that does not require a prescription or a consultation with a healthcare professional but may pose other concerns such as stigma, issues related to drug testing at work, and so forth. There is significant policy interest in understanding and improving the work capacity of older adults in the U.S., especially given its implications for social insurance programs (Coile, Milligan, and Wise 2017;Cutler, Meara, and Richards-Shubik 2013;Lopez-Garcia, Maestas, and Mullen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use RML adoption as a large shock to the availability of an alternative form of chronic pain management, in particular one that does not require a prescription or a consultation with a healthcare professional but may pose other concerns such as stigma, issues related to drug testing at work, and so forth. There is significant policy interest in understanding and improving the work capacity of older adults in the U.S., especially given its implications for social insurance programs (Coile, Milligan, and Wise 2017;Cutler, Meara, and Richards-Shubik 2013;Lopez-Garcia, Maestas, and Mullen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Economists are also wellpositioned to explore how the Americans with Disabilities Act (ADA), workplace policies, and access to Social Security Disability Insurance benefits help workers cope with cognitive decline, building on general research on these topics conducted in the past (Acemoglu and Angrist 2001;Hill, Maestas, and Mullen 2016). Recent research estimating work capacity by comparing individuals' self-reported functional abilities to the functional requirements of occupations (Garcia, Maestas, and Mullen 2019) could be adapted to assess the work capacity of those with MCI.…”
Section: Labor Supplymentioning
confidence: 99%
“…We also study a host of complementary measures to help determine whether changes in WC benefit receipt reflect changes in work capacity for the affected population instead of other possible economic and behavioral responses to RML adoption. Our focus on work capacity is due to the significant policy interest in improving this metric among older adults in the U.S., especially given its implications for social insurance program expenditures (Coile et al., 2017; Cutler et al., 2013; Lopez‐Garcia et al., 2019). We study WC as a useful metric of work capacity for this population and due to policy interest in the determinants of WC benefit receipt.…”
Section: Introductionmentioning
confidence: 99%